2016
DOI: 10.1270/jsbbs.66.90
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity of the wild Ussurian pear in East Asia

Abstract: The Ussurian pear is the most important cultivated pear in the northern part of China. Cultivated Ussurian pears are considered to have derived from Pyrus ussuriensis Maxim. which is native to the northeast of China. In Japan, two varieties of P. ussuriensis, P. ussuriensis var. aromatica and var. hondoensis are native to the northern area and the central area of the main island respectively. In order to reveal the origin of Pyrus ussuriensis var. aromatica distributed in the northern area of main island of Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Whether this species began to be used before or after introgression is still unknown. This is discussed in more detail by Katayama (2016) in this issue.…”
Section: Regional Usage Of Fruits and Nutsmentioning
confidence: 88%
“…Whether this species began to be used before or after introgression is still unknown. This is discussed in more detail by Katayama (2016) in this issue.…”
Section: Regional Usage Of Fruits and Nutsmentioning
confidence: 88%
“…European cultivars all belong to the species P. communis. Cultivated species of Asian pears include the Ussurian pear (P. ussuriensis Maxim), Chinese white pear (P. × bretschneideri Rehder), Chinese sand pear and Japanese pear (P. pyrifolia Nakai) and Xinjiang pear (P. sinkiangensis Yu) [4,5]. Bao et al [4] suggested that the progenitor of Japanese pears originated from China.…”
Section: Introductionmentioning
confidence: 99%
“…Pear (Pyrus spp.) is one of the economically and nutritionally valuable and popular rosaceous fruit crop being cultivated in temperate climates, it originated in the mountain regions of south-western China and have spread all over the world (1,2). It considered as the third most significant fruit crop after grapes and apples in temperate areas (3).…”
Section: Introducctionmentioning
confidence: 99%
“…The genus Pyrus (2n = 34 chromosomes), which belong to the tribe Pyreae, subfamily Pomoideae in the Rosaceae family, is widely distributed on six continents particularly in Asia, Europe, and Africa (3,5,1,6). Classically, based on domestication and the geographical distribution, Pyrus species are divided into two major native groups.…”
Section: Introducctionmentioning
confidence: 99%
See 1 more Smart Citation